Construção e validação do jogo de tabuleiro para a prevenção de autolesão não suicida em adolescentes - Quintiliano, Guilherme Luis Nascimento (2023)
Adolescence is a phase conducive to presenting doubts and uncertainties as a result of the biological, psychological and emotional transformations they experience and the influences that may exist in the context in which they are inserted. In this period of the life cycle, non-suicidal self-harm can emerge with serious consequences for teenagers and adults. The present investigation is justified by the increase in the number of cases of non-suicidal self-injury in adolescents, starting with a public health problem. Objective: To build and validate a board game to prevent non-suicidal self-injury in adolescents. Methods: This is descriptive research with a methodological design that aimed to build and validate a board game based on scientific evidence for the prevention of non-suicidal self-injury in adolescents. Results: It was evidenced through the integrative review that non-suicidal self-injury is a reality in the lives of adolescents, and that the repercussions of this behavior can directly affect the quality of life of adolescents. The synthesis of the studies provided knowledge of the available evidence and the expansion of knowledge about non-suicidal self-injury and enabled the construction of the board game “It's Your Choice”, which consists of a playful and innovative tool based on scientific evidence, validated by expert judges and adolescent judges, through a content validation instrument, which made it possible to evaluate each individual game item and the instrument as a whole, validated by expert judges and adolescent judges, through a content validation instrument, which made it possible to evaluate each individual game item and the instrument as a whole. The Content Validation Index was used, and the instrument obtained an agreement rate of 1.0 by the expert judges, the rate obtained by the adolescent judges 0.80 and the general rate of the instrument obtained was 0.92. Conclusion: The ludic and innovative tool is a strategy that can contribute to professional practice in the area of education and health in the context of adolescents, minimizing the repercussions of this problem in their daily lives and that of their families, as well as contributing to the production of scientific knowledge and future research. It is essential to develop or use teaching methodologies that are effective for adolescent learning, whether in the school environment, with education professionals or in health units, through the nurse, since the nurse is an agent of promotion and education in health, in this context, the use of playful, didactic and innovative tools can be fundamental.